ANALISIS KUALITAS PROSES PRODUKSI LISTRIK MENGGUNAKAN DIAGRAM FISHBONE PADA PLT - BIO GAS 1 MW DESA RANTAU SAKTI KABUPATEN ROKAN HULU - , Prima Andreas Siregar, Ismaya , Iwan Nauli Daulay (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the problems faced by the Biogas Power Plant Company in Rantau Sakti Village, Rokan Hulu Regency related to the quality of the electricity products produced, identify the most dominant factors and formulate the most appropriate solutions to be applied in increasing electricity products. The method used in this research is a quantitative descriptive method. The analytical methods used are (1) questionnairy to determine the problem (2) pareto chart to identify the most dominant factor (3) fishbone chart to analyze what factors affect the quality of electricity. The factors that influence the quality of electrical products at the Biogas Power Plant Company in Rantau Sakti Village, Rokan Hulu Regency are as follows: (a) Machines (b) Maintenance (c) Humans (d) Materials. (2) the most dominant factor influencing the electricity production process in a biogas power plant company is the machine, namely the machine is not working optimally and the company has not had enough availability of the machine. (3) The most appropriate improvement efforts implemented by the Biogas Power Plant Company are carrying out routine engine maintenance. The company should carry out inspections of machine tools. Keywords: Fishbone Analysis, Production Process Quality